2023
DOI: 10.1002/aenm.202301665
|View full text |Cite
|
Sign up to set email alerts
|

Highly Integrated Triboelectric‐Electromagnetic Wave Energy Harvester toward Self‐Powered Marine Buoy

Abstract: This paper proposes a highly integrated triboelectric‐electromagnetic wave energy harvester (TEWEH) that can efficiently collect wide‐frequency wave energy and realize a self‐powered marine buoy. The innovative design of a permanent magnet‐polytetrafluoroethylene (PM‐PTFE) ball ensures high integration between the magnetic material forming the electromagnetic generator (EMG) and the dielectric material forming the triboelectric nanogenerator (TENG). In the condition of swinging (1 Hz and ±30°), the output of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Zhang et al used multiple PTFE balls moving inside the buoy structure BEH and found its peak power reached 61.20 mW when the wave height was 6 cm [82]. Furthermore, Zhu et al proposed a highly integrated triboelectric-electromagnetic wave energy collector (TEWEH) that was applied to roll permanent magnet PTFE balls [83]. The TEWEH had been demonstrated as a self-powered marine buoy deployed near Dalian Bay and transmitted measurements to the receiver.…”
Section: Buoy Structural Teng Applied In Blue Energy Harvestingmentioning
confidence: 99%
“…Zhang et al used multiple PTFE balls moving inside the buoy structure BEH and found its peak power reached 61.20 mW when the wave height was 6 cm [82]. Furthermore, Zhu et al proposed a highly integrated triboelectric-electromagnetic wave energy collector (TEWEH) that was applied to roll permanent magnet PTFE balls [83]. The TEWEH had been demonstrated as a self-powered marine buoy deployed near Dalian Bay and transmitted measurements to the receiver.…”
Section: Buoy Structural Teng Applied In Blue Energy Harvestingmentioning
confidence: 99%
“…(The image in (i) has been reproduced with permission. [41,[44][45][46][47] the rabbit fur moves past the FEP membrane of the stator during rotation. Due to the triboelectric effect, electrons are transferred from the regular bristles to the FEP membrane.…”
Section: Device Structure and Working Principlementioning
confidence: 99%
“…The experimental system subsequently evaluated the output performance of both the TENG and EMG components of the entire device, revealing that the power density surpasses that of previous devices. [44][45][46][47] The detailed data and comparisons with more state-of-the-art devices are summarized in Table S1 (Supporting Information). With appropriate circuit management, the combined output of the entire device fully demonstrates the advantages of integrating TENG and EMG technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the triboelectric nanogenerator (TENG) is an excellent choice based on the coupling of triboelectrification and electrostatic induction first proposed by Wang’s group in 2012 and is regarded an emerging self-powered sensing technology, , which has a widespread application in biomedical, ocean energy harvesting, , and self-powered wearable devices. , The easy and on-site manufacturing and repair of the TENG can be the most valuable feature for outer space applications. First, the TENG boasts unique advantageous features with simple structure, easy fabrication, and high sensitivity in space debris, which easily integrates into the surface of spacecraft or space station to achieve precise monitoring of small impacts, facilitating detection and localization, reducing costs, and enhancing the reliability and stability. Second, compared to traditional energy supply methods, TENG converts mechanical energy into electrical energy, utilizing electrostatic induction to generate self-powered signals through collisions in space without the need for additional energy supply, thereby eliminating the need for additional energy supply. The characteristic bestows the TENG with sustainability and self-sufficiency during prolonged space missions, reducing reliance on external power sources.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the triboelectric nanogenerator (TENG) is an excellent choice based on the coupling of triboelectrification and electrostatic induction first proposed by Wang 2012 and is regarded an emerging self-powered sensing technology, 5,6 which has a widespread application in biomedical, 7−9 ocean energy harvesting, 10,11 and self-powered wearable devices. 12,13 The easy and on-site manufacturing and repair of the TENG can be the most valuable feature for outer space applications.…”
Section: Introductionmentioning
confidence: 99%